THE SIMILARITY AND DIFFERENCE VOCABULARY BETWEEN INDONESIA LANGUAGE AND PATTANI MALAY USED BY THAI STUDENTS STUDYING IN INDONESIA - Seetee A-E-Soh Sama-ae; Ria Kamilah Agustina (Teaching English as Foreign Language, Literature and Linguistics, 2023)
This study aims to find out the difference and the similarity vocabulary between Indonesia Language and Pattani Malay used by Thai students studying in Indonesia. This research method is descriptive qualitative. The source of research data is speech in the form of sentences or words spoken by Thai Students studying in Indonesia. This research data collection technique is a technique of listening to conversations, recordings, recordings, and interviews, most recently analyzing them. Data analysis techniques using contrastive analysis methods. The results of this study are three, first, the breadth of Indonesia Language is wider than Pattani Malay. Second, some words in Indonesian and Pattani Malay have the same meaning as the same voice and speech as vocabulary in both languages. Third, some Indonesian words and Pattani Malay language that have very different meanings although in terms of the same designation.